Porous polymer powder, its composition, its use and composition containing the same

By using a porous polymer powder with a total invasive volume of at least 1.2 ml/g, the problem of the difficulty of dispersing the polymer impact modifier in liquid resin or monomer is solved, and the rapid and uniform dispersion of the polymer composition and impact resistance are achieved. Performance improvement.

CN114729083BActive Publication Date: 2025-01-03ARKEMA FRANCE SA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080082490.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-30
Publication Date
2025-01-03
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

Existing polymer impact modifiers are difficult to disperse quickly and uniformly in liquid resins or monomers, affecting the performance of the final polymer composition.

Method used

Using a porous polymer powder with a total invasion volume of at least 1.2 ml/g, measured by the mercury porosity method, it can be dispersed quickly and uniformly in the liquid resin or monomer, providing good impact resistance.

Benefits of technology

The rapid and uniform dispersion of polymer powder in liquid resin or monomer is achieved, which significantly reduces the dispersion time and improves the impact resistance of the polymer composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 270046
    Figure 270046
Patent Text Reader

Abstract

The present invention relates to a polymer composition in the form of a porous polymer powder, its composition and its use. In particular, the present invention relates to a porous polymer powder comprising a polymer in the form of polymer particles produced by a multistage process. The present invention also relates to the use of the porous polymer powder and a composition comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] [Field of the Invention]

[0002] The present invention relates to polymer compositions in the form of porous polymer powders, their compositions and their use.

[0003] In particular, the present invention relates to porous polymer powders comprising a polymer in the form of polymer particles produced by a multistage process.

[0004] The present invention also relates to the use of the porous polymer powder and a composition containing the same.

[0005] [Technical issues]

[0006] Polymers are also widely used as additives in polymer compositions. These polymer additives are usually added to solid polymers as granules or as powders, or to molten polymers, or to liquid resins, or to liquid compositions.

[0007] One class of polymer additives are processing aids and another class of polymer additives are polymer impact modifiers.

[0008] Typically, polymeric impact modifiers in the form of core-shell particles are made by a multistage process, where at least one stage contains a rubber-like polymer. These particles are then incorporated into polymers or polymer compositions to improve their impact resistance.

[0009] Another class of polymer additives are polymer particles which are used, for example, for light scattering or diffusion of the polymer matrix or for surface roughness or glossiness of the polymer surface.

[0010] Typically, scattering polymer particles are made from polymers that are cross-linked to some extent in order to maintain the particle form.

[0011] Thermosetting polymers consist of a cross-linked three-dimensional structure. The cross-linking is obtained by curing reactive groups within the so-called prepolymer. Curing can be achieved, for example, by heating the polymer chains or prepolymers to permanently cross-link and harden the material.

[0012] Thermoplastic polymers consist of linear or branched polymers which are usually not crosslinked.

[0013] However, such core-shell particles or scattering particles do not disperse easily or quickly in all kinds of resins or polymers or polymer precursors, especially for example in liquid epoxy resins or liquid monomers or other liquid polymer precursors.

[0014] In order for the final polymer composition to have satisfactory impact resistance or scattering properties, good uniform and rapid dispersion is necessary.

[0015] One object of the present invention is to propose a polymer composition in the form of a polymer powder which is quickly and easily dispersible, especially in liquid resins such as thermosetting polymers or precursors of thermoplastic polymers, such as epoxy resins or (meth)acrylic monomers, respectively.

[0016] Another object of the present invention is to propose a polymer composition in the form of a dry polymer powder which is easily dispersible in particular in liquid resins such as epoxy resins or (meth)acrylic monomers.

[0017] A further object of the invention is the use of a polymer composition in the form of a polymer powder for the preparation of a liquid composition comprising a precursor of a thermosetting polymer or a thermoplastic polymer, such as a liquid reactive epoxy resin or a (meth)acrylic monomer, in which said polymer composition is dispersed.

[0018] Yet another object is to reduce the dispersion time of the polymer powder in the liquid composition.

[0019] Yet another additional object is to propose an impact modifier in the form of a polymer powder which is quickly and easily dispersible, especially in liquid resins such as thermosetting polymers or precursors of thermoplastic polymers, such as epoxy resins or (meth)acrylic monomers, respectively.

[0020] [Background of the invention] Prior art

[0021] Document US2004 / 0147668 discloses acrylic polymer powder, acrylic sol and molded product. The acrylic polymer powder has an average particle size of 5 to 10 μm and a void volume of 0.9 ml / g or less in voids with a pore size of 1 μm or more.

[0022] Document EP2196479 discloses vinylidene fluoride polymer powder and its use. The polymer powder is prepared by supercritical suspension polymerization, and the volume of pores with a pore size of 0.03 µm to 1.0 µm measured by mercury porosimetry is 70 volume % to 93 volume % of the total pore volume.

[0023] Document WO2017 / 121749 discloses a liquid composition comprising a multi-stage polymer. In particular, a liquid composition comprising a monomer, a (meth) acrylic polymer and a multi-stage polymer is disclosed.

[0024] None of the prior art documents discloses a polymer composition in powder form having a porosity expressed as a total intrusion volume of at least 1.2 ml / g as measured by mercury intrusion porosimetry.

[0025] [Brief description of the invention]

[0026] Surprisingly, it has been found that a polymer composition in the form of a porous polymer powder POW1 can be easily and quickly dispersed in other polymers, liquid resins and / or monomers if the total intrusion volume of the powder is at least 1.2 ml / g measured by mercury porosimetry.

[0027] Surprisingly, it has also been found that a polymer composition in the form of a porous polymer powder POW1 comprising polymer particles can be easily and quickly dispersed in other polymers and liquid resins if the total intrusion volume of the powder is at least 1.2 ml / g measured by mercury porosimetry.

[0028] Surprisingly, it has also been found that a polymer composition in the form of a porous polymer powder POW1 comprising polymer particles can be easily and quickly dispersed uniformly in other polymers and liquid resins to provide satisfactory impact resistance if the total intrusion volume of the powder is at least 1.2 ml / g measured by mercury porosimetry.

[0029] Surprisingly, a process has also been found for preparing a liquid polymer composition LPC1 comprising the following steps:

[0030] a) providing a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g as measured by mercury porosimetry,

[0031] b) contacting the polymer composition with a liquid composition LC1,

[0032] A liquid polymer composition is obtained in which the polymer composition POW1 is uniformly and rapidly dispersed in the liquid composition LC1.

[0033] Surprisingly, it has also been found that a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g as measured by mercury porosimetry can be used to prepare a liquid polymer composition.

[0034] Surprisingly, it has also been found that a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g measured by mercury porosimetry can be used to reduce the time for dispersing the porous polymer powder POW1 in order to obtain a liquid polymer composition.

[0035] Surprisingly, a method has also been found for reducing the dispersion time of a polymer composition in a liquid composition, comprising the steps of:

[0036] a) providing a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g as measured by mercury porosimetry,

[0037] b) contacting the polymer composition with a liquid composition LC1,

[0038] The process is faster than the same process using a polymer composition in the form of a polymer powder having a lower total intrusion volume as measured by mercury porosimetry. [Detailed description of the invention]

[0040] According to a first aspect, the present invention relates to a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g as measured by mercury porosimetry.

[0041] According to a second aspect, the present invention relates to a method for preparing a liquid polymer composition LCP1 comprising the following steps:

[0042] a) providing a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g measured according to mercury porosimetry,

[0043] b) contacting the polymer composition in the form of porous polymer powder POW1 with a liquid composition LC1.

[0044] In a third aspect, the invention relates to the use of a polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g measured according to mercury porosimetry for reducing the dispersion time of said polymer powder POW1 in a liquid composition LC1.

[0045] In a fourth aspect, the present invention relates to a method for reducing the dispersion time of a polymer composition, characterized in that the polymer composition is in the form of a polymer powder POW1 having a total intrusion volume in the polymer composition of at least 1.2 ml / g measured according to mercury porosimetry.

[0046] The term "polymer powder" as used herein means a polymer in powder form comprising powder particles in the range of at least 1 µm obtained by agglomeration of primary polymer particles comprising one or more polymers in the nanometer range.

[0047] The term "primary particles" used refers to spherical polymers comprising particles in the nanometer range. Preferably, the weight average particle size of the primary particles is between 50 nm and 1000 nm.

[0048] The term "particle size" as used herein refers to the volume average diameter of the particles.

[0049] The term "thermoplastic polymer" as used herein refers to a polymer that becomes liquid or becomes more liquid or less viscous when heated and that can assume new shapes by the application of heat and pressure.

[0050] The term "thermosetting polymer" is used to denote a prepolymer in a soft, solid or viscous state that irreversibly changes by curing to an infusible and insoluble polymer network.

[0051] The term "polymer composite" is used to refer to a multi-component material comprising a plurality of distinct domains, wherein at least one type of domain is a continuous phase, and wherein at least one component is a polymer.

[0052] The term "copolymer" is used to indicate that the polymer consists of at least two different monomers.

[0053] As used herein, "multistage polymer" means a polymer formed in a sequential manner by a multistage polymerization process. Preferred are multistage emulsion polymerization processes in which the first polymer is a first stage polymer and the second polymer is a second stage polymer, i.e., the second polymer is formed by emulsion polymerization in the presence of a first emulsion polymer, wherein at least two stages differ in composition.

[0054] The term "(meth)acrylic" is used to denote all classes of acrylic and methacrylic monomers.

[0055] The term "(meth)acrylic polymer" used means that the (meth)acrylic polymer substantially includes a polymer containing 50% by weight or more of a (meth)acrylic monomer based on the (meth)acrylic polymer.

[0056] The term "dry" is used to mean that the proportion of residual water is less than 1% by weight.

[0057] The range of x to y mentioned in the present invention means including the upper limit and the lower limit of the range, which is equivalent to at least x and at most y.

[0058] The range between x and y mentioned in the present invention does not include the upper limit and the lower limit of the range, which is equivalent to being greater than x and less than y.

[0059] The term "total intrusion volume" used here means the total volume intruded by liquid mercury according to ISO 15901-1:2016. This volume is accumulated and the results of the analysis are displayed in ml / g (cm 3 The cumulative intrusion volume in units of 100 μg / g) is the change in applied pressure or pore size. The total intrusion volume is the volume intruded at the maximum applied pressure, which also corresponds to the smallest pore.

[0060] The term "incremental intrusion" used here means the volume in ml / g that intrudes between two specific pressures or two pore sizes. This incremental intrusion can also be expressed in volume % relative to the total intrusion volume.

[0061] Readily dispersible in the liquid resin means that a uniform dispersion is obtained. If separation occurs after initial homogenization, the distribution of the polymer composition is non-uniform.

[0062] Rapid dispersion in a liquid resin means that a uniform dispersion is achieved more quickly than in a polymer composition whose porosity does not meet the minimum requirement.

[0063] The polymer composition according to the invention is in the form of larger polymer particles: a porous polymer powder POW1 having a total intrusion volume or total cumulative intrusion of at least 1.2 ml / g measured by mercury porosimetry. The polymer powder POW1 particles comprise aggregated primary polymer particles PAR1.

[0064] Regarding the polymer powder POW1 of the present invention, its volume median particle size D50 is between 1µm and 700µm. Preferably, the volume median particle size of the polymer powder is between 10µm and 600µm, more preferably between 15µm and 550µm, and advantageously between 20µm and 500µm.

[0065] The particle size distribution D10 by volume is at least 7 μm, and preferably 10 μm, more preferably 15 μm.

[0066] The particle size distribution D90 by volume is at most 1000 μm, and preferably 950 μm, more preferably at most 900 μm, and even more preferably at most 800 μm.

[0067] The porosity of the polymer powder POW1 is expressed as the total intrusion volume or the total cumulative intrusion amount (cumulative intrusion volume) in milliliters (ml) of mercury per mass (g) of the polymer powder POW1. This is measured according to standard ISO 15901-1: Evaluation of pore size distribution and porosity of solid materials by mercury porosity and gas adsorption – Part 1: mercury porosity. The total intrusion volume or the total cumulative intrusion amount of the porous polymer powder POW1 of the present invention is at least 1.2 ml / g, preferably 1.25 ml / g, more preferably 1.3 ml / g, even more preferably 1.35 ml / g. The total cumulative intrusion amount is taken into account before the pore diameter of 0.005 µm. Preferably, the total intrusion volume or the total cumulative intrusion amount is taken into account between the pore diameters of 100 µm and 0.005 µm or at pressures between 0.01 MPa and 400 MPa.

[0068] The total intrusion volume or total cumulative intrusion amount of the porous polymer powder POW1 of the present invention is at most 10 ml / g. Preferably, the total intrusion volume is at most 8 ml / g, more preferably at most 7 ml / g, even more preferably at most 6 ml / g, advantageously at most 5 ml / g, and most advantageously at most 4 ml / g.

[0069] The respective upper and lower limits of the total intrusion volume or the total cumulative intrusion amount of the porous polymer powder POW1 of the present invention given in the first two paragraphs may be combined in any combination of an upper limit and a lower limit.

[0070] Preferably, the total intrusion volume or total cumulative intrusion amount of the porous polymer powder POW1 of the present invention is between 1.2 ml / g and 10 ml / g, more preferably between 1.25 ml / g and 8 ml / g, even more preferably between 1.3 ml / g and 7 ml / g, advantageously between 1.35 ml / g and 6 ml / g, more advantageously between 1.35 ml / g and 5 ml / g, and most advantageously between 1.35 ml / g and 4 ml / g.

[0071] The incremental intrusion (incremental intrusion volume) represents the volume between two specific pore sizes. The incremental intrusion can be expressed as an absolute value, also in ml / g, or as a relative value as a percentage of the total intrusion volume or the total cumulative intrusion (considered between pore sizes of 100 µm and 0.005 µm).

[0072] Preferably, the porous polymer powder POW1 of the present invention has a cumulative intrusion amount of at least 0.9 ml / g, more preferably at least 1 ml / g, for pore sizes exceeding 10 μm (greater than 10 μm).

[0073] Preferably, the porous polymer powder POW1 of the present invention has a relative incremental intrusion of pore sizes above 10 µm (greater than 10 µm) of at most 85%, more preferably at most 82%, and even more preferably at most 80%.

[0074] Preferably, the porous polymer powder POW1 of the present invention has an incremental intrusion between pore sizes of 10 µm and 1 µm of at least 0.1 ml / g, more preferably at least 0.12 ml / g, and even more preferably at least 0.15 ml / g.

[0075] Preferably, the porous polymer powder POW1 of the present invention has a relative incremental intrusion between pore sizes of 10 µm and 1 µm of at least 5%, more preferably at least 8%, and even more preferably at least 10%.

[0076] Preferably, the porous polymer powder POW1 of the present invention has an incremental intrusion between pore sizes of 10 µm and 0.1 µm of at least 0.15 ml / g, more preferably at least 0.2 ml / g, and even more preferably at least 0.25 ml / g.

[0077] Preferably, the porous polymer powder POW1 of the present invention has a relative incremental intrusion between pore sizes of 10 µm and 0.1 µm of at least 10%, more preferably at least 15%, and even more preferably at least 20%.

[0078] Preferably, the porous polymer powder POW1 of the present invention has an incremental intrusion between pore sizes of 1 µm and 0.1 µm of at least 0.05 ml / g, more preferably at least 0.06 ml / g, and even more preferably at least 0.07 ml / g.

[0079] Preferably, the porous polymer powder POW1 of the present invention has a relative incremental intrusion between pore sizes of 1 µm and 0.1 µm of at least 5%, more preferably at least 7.5%, and even more preferably at least 10%.

[0080] The apparent bulk density of polymer powder POW1 is less than 0.60 g / cm 3 Preferably, the apparent bulk density is less than 0.45 g / cm 3 , more preferably less than 0.43 g / cm 3 , and even more preferably less than 0.41 g / cm 3 .

[0081] The apparent bulk density of polymer powder POW1 is greater than 0.1 g / cm 3 Preferably, the apparent bulk density is greater than 0.11 g / cm 3 , more preferably greater than 0.12 g / cm 3 , even more preferably greater than 0.13 g / cm 3 .

[0082] The apparent bulk density of polymer powder POW1 is 0.1 g / cm 3 and 0.60g / cm 3 Preferably, the apparent bulk density of the polymer powder POW1 is between 0.12 g / cm 3 and 0.45g / cm 3 between.

[0083] The polymer powder POW1 of the present invention comprises polymer particles PAR1. The polymer particles PAR1 account for at least 50 wt% of the polymer powder composition POW1. More preferably, the polymer particles PAR1 account for at least 60 wt%, and even more preferably at least 70 wt% of the polymer powder composition POW1.

[0084] In a preferred embodiment, the polymer powder POW1 according to the invention consists exclusively of polymer particles PAR1.

[0085] In another preferred embodiment, the polymer powder POW1 according to the invention comprises at least 80% by weight of polymer particles PAR1.

[0086] The polymer particles PAR1 may be one type of particle or a mixture of different types of particles PAR1a and PAR1b. The difference between the different particles PAR1a and PAR1b may be in particle size, polymer composition or particle morphology, or any combination of these three characteristics.

[0087] Regarding the polymer particles PAR1 according to the invention, which are also called primary particles, their weight average particle size (particle diameter) is between 15nm and 900nm. Preferably, the weight average particle size of the polymer particles is between 40nm and 800nm, more preferably between 75nm and 700nm, and advantageously between 30nm and 500nm. The primary polymer particles can be aggregated to obtain the polymer powder POW1 of the invention.

[0088] The particle size distribution may be monodisperse or polydisperse as long as the weight average particle size (particle diameter) is between 15 nm and 900 nm.

[0089] In a first preferred embodiment, the polymer powder POW1 comprises a multistage polymer MSP1 as polymer particles PAR1. The multistage polymer MSP1 is advantageously in the form of core-shell particles, ie polymer particles PAR1.

[0090] In a second preferred embodiment, the polymer powder POW1 comprises a polymer P1. The polymer P1 forms polymer particles PAR1.

[0091] In a third preferred embodiment, the polymer powder POW1 comprises a multistage polymer MSP1 and a (meth)acrylic polymer MP1. In one embodiment, the multistage polymer is in the form of core-shell particles and the (meth)acrylic polymer MP1 is also in the form of polymer particles; a mixture of different particles PAR1a and PAR1b having different polymer compositions and morphologies. In another embodiment, the (meth)acrylic polymer MP1 is part of the multistage polymer, and the two together constitute the polymer particles PAR1.

[0092] The various preferred embodiments of all the different properties of the porous polymer powder POW1 according to the invention can be combined.

[0093] Regarding the (meth)acrylic polymer MP1 of the polymer powder POW1 of the third preferred embodiment, its mass average molecular weight Mw is between 10 000 g / mol and 500 000 g / mol.

[0094] The mass average molecular weight Mw of the (meth)acrylic polymer MP1 is greater than 10,000 g / mol, preferably greater than 10,500 g / mol, more preferably greater than 11,000 g / mol, even more preferably greater than 12,000 g / mol, advantageously greater than 13,000 g / mol, more advantageously greater than 14,000 g / mol, and even more advantageously greater than 15,000 g / mol.

[0095] The mass average molecular weight Mw of the (meth)acrylic polymer MP1 is below 500,000 g / mol, preferably below 450,000 g / mol, more preferably below 400,000 g / mol, even more preferably below 400,000 g / mol, advantageously below 350,000 g / mol, more advantageously below 300,000 g / mol, even more advantageously below 250,000 g / mol, and most advantageously below 200,000 g / mol.

[0096] Preferably, the mass average molecular weight Mw of the (meth)acrylic polymer MP1 is between 10 500 g / mol and 450 000 g / mol, more preferably between 11 000 g / mol and 400 000 g / mol, and even more preferably between 12 000 g / mol and 350 000 g / mol, advantageously between 13 000 g / mol and 300 000 g / mol, more advantageously between 14 000 g / mol and 250 000 g / mol, and most advantageously between 15 000 g / mol and 200 000 g / mol.

[0097] In a first advantageous embodiment, the mass average molecular weight Mw of the (meth)acrylic polymer MP1 is between 10 500 g / mol and 200 000 g / mol, more preferably between 11 000 g / mol and 190 000 g / mol, and even more preferably between 12 000 g / mol and 180 000 g / mol, advantageously between 13 000 g / mol and 150 000 g / mol, more advantageously between 14 000 g / mol and 135 000 g / mol, and most advantageously between 15 000 g / mol and 120 000 g / mol.

[0098] In a second advantageous embodiment, the mass average molecular weight Mw of the (meth)acrylic polymer MP1 is between 15 000 g / mol and 450 000 g / mol, more preferably between 16 000 g / mol and 400 000 g / mol and even more preferably between 17 000 g / mol and 350 000 g / mol, advantageously between 18 000 g / mol and 300 000 g / mol, more advantageously between 19 000 g / mol and 250 000 g / mol and most advantageously between 20 000 g / mol and 200 000 g / mol.

[0099] Preferably, the (meth)acrylic polymer MP1 is a copolymer comprising (meth)acrylic monomers. Even more preferably, the (meth)acrylic polymer MP1 comprises at least 70% by weight of monomers selected from C1-C12 alkyl (meth)acrylates. Advantageously, the (meth)acrylic polymer MP1 comprises at least 80% by weight of C1-C4 alkyl methacrylate monomers and / or C1-C8 alkyl acrylate monomers.

[0100] Preferably, the glass transition temperature Tg of the (meth)acrylic polymer MP1 is between 30° C. and 150° C. More preferably, the glass transition temperature Tg of the (meth)acrylic polymer MP1 is between 40° C. and 150° C., advantageously between 45° C. and 150° C., and more advantageously between 50° C. and 150° C.

[0101] The multistage polymer (MSP1) has a multilayer structure comprising: at least one stage (SA1) comprising a polymer (A1) having a glass transition temperature below 10°C, and at least one stage (SA2) comprising a polymer (A2) having a glass transition temperature above 60°C.

[0102] Preferably, stage (SA1) is the first of the at least two stages and stage (SA2) comprising polymer (A2) is grafted onto stage (SA1) comprising polymer (A1) or onto another optional intermediate layer.

[0103] In a further variant, there may be another stage before stage (SA1), so that stage (SA1) may also be a kind of shell, for example on a seed.

[0104] In a first embodiment, the polymer (A1) having a glass transition temperature of less than 10° C. comprises at least 50% by weight of polymer units derived from alkyl acrylates, and the stage (SA1) is the innermost layer of a multistage polymer (MP1) or a polymer particle having a multilayer structure. In other words, the stage (SA1) comprising the polymer (A1) is the core of the multistage polymer (MP1) or the polymer particle.

[0105] Regarding the polymer (A1) of the first preferred embodiment, it is a (meth)acrylic polymer comprising at least 50% by weight of polymer units derived from acrylic monomers. Preferably 60% by weight and more preferably 70% by weight of polymer (A1) are acrylic monomers.

[0106] The acrylic monomer units in polymer (A1) include monomers selected from C1-C18 alkyl acrylates or mixtures thereof. More preferably, the acrylic monomer units in polymer (A1) include monomers of C2-C12 alkyl acrylic monomers or mixtures thereof. Even more preferably, the acrylic monomers in polymer (A1) include monomers of C2-C8 alkyl acrylic monomers or mixtures thereof.

[0107] The polymer (A1) may contain one or more comonomers copolymerizable with the acrylic monomer as long as the glass transition temperature of the polymer (A1) is lower than 10°C.

[0108] The comonomer(s) in polymer (A1) are preferably selected from (meth)acrylic monomers and / or vinyl monomers.

[0109] Most preferably, the acrylic or methacrylic comonomer of polymer (A1) is selected from methyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate and mixtures thereof, as long as the glass transition temperature of polymer (A1) is below 10°C.

[0110] In one specific embodiment, polymer (A1) is a homopolymer of butyl acrylate.

[0111] More preferably, the glass transition temperature Tg of the polymer (A1) comprising at least 70% by weight of polymer units derived from C2-C8 alkyl acrylate is between -100°C and 10°C, even more preferably between -80°C and 0°C, and advantageously between -80°C and -20°C, and more advantageously between -70°C and -20°C.

[0112] In a second preferred embodiment, the polymer (A1) having a glass transition temperature below 10° C. comprises at least 50% by weight of polymer units derived from isoprene or butadiene, and stage (A) is the innermost layer of the polymer particles having a multilayer structure. In other words, stage (SA1) comprising polymer (A1) is the core of the polymer particles.

[0113] For example, the polymer (A1) of the core of the second embodiment can be mentioned isoprene homopolymer or butadiene homopolymer, isoprene-butadiene copolymer, copolymer of isoprene with up to 98% by weight of vinyl monomer and copolymer of butadiene with up to 98% by weight of vinyl monomer. The vinyl monomer can be styrene, alkylstyrene, acrylonitrile, (meth) alkyl acrylate or butadiene or isoprene. In a preferred embodiment, the core is a butadiene homopolymer.

[0114] More preferably, the glass transition temperature Tg of the polymer (A1) comprising at least 50% by weight of polymer units derived from isoprene or butadiene is between -100°C and 10°C, even more preferably between -90°C and 0°C, advantageously between -85°C and 0°C and most advantageously between -800°C and -20°C.

[0115] In a third preferred embodiment, polymer (A1) is a silicone rubber based polymer. Silicone rubber is, for example, polydimethylsiloxane. More preferably, the glass transition temperature Tg of polymer (A1) of the second embodiment is between -150°C and 0°C, even more preferably between -145°C and -5°C, advantageously between -140°C and -15°C, and more advantageously between -135°C and -25°C.

[0116] As polymer (A2), homopolymers and copolymers containing monomers having double bonds and / or vinyl monomers may be mentioned. Preferably, polymer (A2) is a (meth)acrylic polymer.

[0117] Preferably, polymer (A2) comprises at least 70 wt% of monomers selected from C1-C12 alkyl (meth)acrylates. Even more preferably, polymer (A2) comprises at least 80 wt% of C1-C4 alkyl methacrylates and / or C1-C8 alkyl acrylates.

[0118] Most preferably, the acrylic or methacrylic monomer of polymer (A2) is selected from methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate and mixtures thereof, as long as the glass transition temperature of polymer (A2) is at least 60°C.

[0119] Advantageously, polymer (A2) comprises at least 70% by weight of monomer units derived from methyl methacrylate.

[0120] Preferably, the glass transition temperature Tg of polymer (A2) is between 60 and 150° C. The glass transition temperature of polymer (A2) is more preferably between 80 and 150° C., advantageously between 90 and 150° C. and more advantageously between 100 and 150° C.

[0121] Preferably, the polymer (A2) of the multistage polymer (MP1) is grafted onto the polymer (A1) prepared in a preceding stage.

[0122] In certain embodiments, polymer (A2) is cross-linked.

[0123] In one embodiment, polymer (A2) comprises a functional comonomer. The functional copolymer is selected from acrylic acid or methacrylic acid, an amide derived from the acid (e.g. dimethylacrylamide), 2-methoxyethyl acrylate or 2-methoxyethyl methacrylate, optionally quaternized 2-aminoethyl acrylate or 2-aminoethyl methacrylate, polyethylene glycol (meth) acrylate, a water-soluble vinyl monomer (e.g. N-vinyl pyrrolidone) or a mixture thereof. Preferably, the molecular weight of the polyethylene glycol group of the polyethylene glycol (meth) acrylate is from 400 g / mol to 10000 g / mol.

[0124] As regards the liquid composition LC1 which is contacted with the porous polymer powder POW1 according to the invention in the method according to the second aspect of the invention, it is or comprises a precursor of a thermosetting polymer or a monomer of a thermoplastic polymer.

[0125] The viscosity of the liquid composition LC1 is between 0.5 mPa*s and 1000 Pa*s at a temperature of 25° C. The viscosity is the dynamic viscosity.

[0126] The liquid polymer composition LCP1 prepared in the process according to the second aspect of the invention has a viscosity at a temperature of 25° C. between 10 mPa*s and 100 000 Pa*s. The viscosity is a dynamic viscosity.

[0127] For example, the liquid composition LC1 may be selected from compositions for preparing vinyl ester, unsaturated polyester or epoxy resin; or it may be, for example, a styrenic monomer or a (meth)acrylic monomer, or a mixture thereof, or a liquid composition comprising the monomer.

[0128] Preferably, the weight percentage of the porous polymer powder POW1 to the liquid polymer composition LCP1 is between 0.5 wt % and 50 wt %.

[0129] The method for reducing the dispersion time comprises at least the step of providing the polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g as measured by mercury porosimetry.

[0130] The provided method also optionally comprises the step of providing a precursor of a thermosetting polymer or a monomer of a thermoplastic polymer. Preferably, the precursor is a liquid. More preferably, the viscosity of the precursor at a temperature of 25° C. is between 0.5 mPa*s and 1000 Pa*s. The viscosity is a dynamic viscosity.

[0131] The method of reducing dispersion time further optionally comprises the step of contacting a polymer composition in the form of a porous polymer powder POW1 with the precursor. Preferably, between 0.5 and 100 parts by weight of porous polymer powder POW1 are contacted with 100 parts by weight of the precursor.

[0132] The invention also relates to the use of the polymer composition in the form of a polymer powder according to the invention as an impact modifier in a polymer to obtain an impact-modified polymer composition. Preferably, the polymer is a thermosetting polymer or a precursor thereof or a thermoplastic polymer or a precursor thereof.

[0133] [Evaluation method]

[0134] Glass transition temperature

[0135] The glass transition (Tg) of the polymer was measured using equipment capable of thermomechanical analysis. The RDAII "RHEOMETRICS DYNAMIC ANALYSER" provided by Rheometrics Company was used. Thermomechanical analysis accurately measures the changes in viscoelasticity of a sample as a function of applied temperature, strain or deformation. The equipment continuously records the sample deformation while maintaining the strain constant during a controlled program of temperature changes.

[0136] The results are obtained by plotting the elastic modulus (G'), loss modulus and tan delta as a function of temperature. Tg is the highest temperature value read in the tan delta curve when the derivative of tan delta equals 0.

[0137] Molecular weight

[0138] The mass average molecular weight (Mw) of the polymer was measured by size exclusion chromatography (SEC). Polystyrene standards were used for calibration. The polymer was dissolved in THF at a concentration of 1 g / L. The chromatographic column used modified silica. The flow rate was 1 ml / min and a refractive index detector was used.

[0139] Particle size analysis

[0140] The particle size of the primary particles after multi-stage polymerization was measured using a Zetasizer with dynamic light scattering. The weight average particle size (particle diameter) was used as the result.

[0141] The particle size of the reconstituted polymer powder was measured using a Malvern Mastersizer 3000 with laser diffraction from MALVERN.

[0142] For the evaluation of the weight-average particle size, particle size distribution and fine particle ratio of the powders, a Malvern Mastersizer 3000 with a 300 mm lens and a measuring range of 0.5-880 µm was used.

[0143] Porosity

[0144] The porosity is measured as the cumulative intrusion of mercury into the porous structure. The standard ISO 15901-1:2016, "Evaluation of pore size distribution and porosity of solid materials by mercury porosity and gas adsorption – Part 1: mercury porosity", is used. As equipment, the AutoPore from Micromeritics® was used. TM IV model 9500. As a result, the following Figure 1 Cumulative intrusion as a function of pore size is shown in .

[0145] Dispersion test, a sample of each powder is dispersed in a liquid composition. The results of the dispersion test are given with symbols "++" to "-". This indicates how quickly and easily the powder is dispersed in the liquid composition. The symbol "-" indicates a poor dispersion, and the powder may still be separated after the dispersion test, either floating, sinking or other phase separation. The symbol "+" or the symbol "++" indicates good instant dispersion or very good instant dispersion. In the embodiment, the monomer methyl methacrylate (MMA) is used as a liquid composition. In a glass container containing 99g of MMA, 1g of each powder is added at 25°C. Without stirring, observe whether the powder is dispersed in the mixture after 60 seconds.

[0146] Apparent density

[0147] Use standard ISO 60: 1977. Pour the sample through a specific funnel into a 100 cm3 measuring cylinder, remove the excess with a ruler and determine the mass of the contents by weighing.

[0148] Viscosity

[0149] Viscosity can be easily measured using a rheometer or a viscometer. Dynamic viscosity is measured at 25°C. If the liquid has Newtonian behavior, i.e., no shear thinning, the dynamic viscosity is independent of the shear action in the rheometer or the moving speed in the viscometer. If the liquid composition has non-Newtonian behavior, i.e., shear thinning, the dynamic viscosity is measured at 25°C in 1 s. -1 The dynamic viscosity is measured at a shear rate of 1.

[0150] [Example]

[0151] The following polymer powders were tested:

[0152] Comparative Example 1: A powder made of a core / shell polymer having a butadiene core and a (meth)acrylic shell was used. The total intrusion volume of the product was 0.945 ml / g and Figure 1 In the figure, it is shown as a diamond (solid symbol). Figure 1 In Figure 1, the intrusion volume of mercury (in ml / g) is shown as a function of the pore size (in μm). The intrusion volume is cumulative, and the total intrusion volume is the volume at the smallest pore size.

[0153] Comparative Example 2: MBS core-shell powder was used. The total intrusion volume of the product was 1.07 ml / g and Figure 1 It is shown by circles (solid symbols).

[0154] Comparative Example 3: A powder named EXL2691A from Röhm and Haas Company was used. The total intrusion volume of this product was 1.16 ml / g and Figure 1 It is shown with diamonds (open symbols).

[0155] Example 1: MBS core-shell powder, with a total intrusion volume of 1.46 ml / g, and Figure 1 In the figure, it is shown with squares (open symbols).

[0156] Example 2: MBS core-shell powder, with a total intrusion volume of 1.53 ml / g, and Figure 1 It is shown with triangles (open symbols).

[0157] Example 3: MBS core-shell powder, with a total intrusion volume of 1.51 ml / g and Figure 1 It is shown with triangles (solid symbols).

[0158] Example 4: MBS core-shell powder, with a total intrusion volume of 2.02 ml / g, and Figure 1 It is shown in the figure with squares (solid symbols).

[0159] Example 5: MBS core-shell powder, with a total intrusion volume of 2.47 ml / g, and Figure 1 It is shown by circles (open symbols).

[0160] Table 1 - Individual powder characteristics - particle size and particle size distribution

[0161] D10 [µm] D50 [µm] D90 [µm] Comparative Example 1 60 140 260 Comparative Example 2 160 800 2000 Comparative Example 3 30 100 250 Example 1 90 350 880 Example 2 50 150 650 Example 3 30 80 160 Example 4 43 85 215 Example 5 40 80 200

[0162] Figure 1 The cumulative intrusion is shown as a function of pore size for each sample. The cumulative intrusion of mercury in ml / g is given for pore sizes between 100 µm and 0.003 µm. The total intrusion volume, bulk density and dispersion test results for each sample are given in Table 2.

[0163] Figure 1 The data in are further elaborated at specific increments of pore diameter. These data are shown in Tables 3 and 4.

[0164] Table 2 - Results of mercury porosimetry and dispersion testing

[0165] Total intrusion volume [ml / g] <![CDATA[Bulk density [g / cm 3 > Decentralized testing Comparative Example 1 0.945 0.498 - Comparative Example 2 1.07 0.419 - Comparative Example 3 1.16 0.433 - Example 1 1.46 0.362 + Example 2 1.53 0.334 + Example 3 1.51 0.422 + Example 4 2.02 0.271 ++ Example 5 2.47 0.248 ++

[0166] Table 3 - Results of mercury porosimetry

[0167] Relative incremental intrusion volume for pores > 10 µm [%] Incremental intrusion volume for pores > 10 µm [ml / g] Relative incremental intrusion of pore volume between 10µm and 1µm [%] Incremental intrusion for pore volume of 10µm-1µm [ml / g] Comparative Example 1 83 0.78 6 0.078 Comparative Example 2 86 0.93 6 0.075 Comparative Example 3 66 0.77 14 0.15 Example 1 80 1.18 14 0.19 Example 2 66 1.00 18 0.26 Example 3 75 1.15 16 0.26 Example 4 67 1.32 17 0.34 Example 5 66 1.64 16 0.38

[0168] Table 4 - Results of mercury porosimetry

[0169] Relative incremental intrusion of pore volume between 10µm and 0.1µm [%] Incremental intrusion for pore volume of 10µm-0.1µm [ml / g] Relative incremental penetration of pore volume between 1µm and 0.01µm [%] Incremental intrusion for pore volume of 1µm-0.01µm [ml / g] Comparative Example 1 14 0.13 5 0.05 Comparative Example 2 7.4 0.08 1.4 0.015 Comparative Example 3 27 0.31 11.4 0.13 Example 1 16 0.23 4 0.05 Example 2 29 0.45 12 0.18 Example 3 21 0.31 5 0.075 Example 4 31 0.61 15 0.30 Example 5 30 0.74 15 0.37

[0170] Tables 3 and 4 show that in addition to a total intrusion volume of at least 1.2 ml / g, it is also important to have an incremental intrusion of at least 0.9 ml / g for pore volume above 10 µm, at least 0.15 ml / g for pore volume from 10 µm to 1 µm, at least 0.2 ml / g for pore volume from 10 µm to 0.1 µm, and at least 0.05 ml / g for pore volume from 1 µm to 0.01 µm.

[0171] As shown in the last column of Table 2, the powder composition examples according to the invention disperse faster in the monomeric MAM than the comparative powder examples.

Claims

1. A polymer composition in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g measured according to mercury porosimetry, characterized in that The incremental intrusion between pore sizes of 10 μm and 1 μm is at least 0.12 ml / g, and the relative incremental intrusion between pore sizes of 10 μm and 1 μm is at least 8%, and the polymer powder POW1 contains polymer particles PAR1 accounting for at least 50 weight % of the polymer powder composition POWl; wherein the polymer particles PAR1 include a multi-stage polymer MSP1.

2. The polymer composition according to claim 1, characterized in that The total intrusion volume is at least 1.35 ml / g as measured by mercury porosimetry.

3. The polymer composition according to claim 1 or 2, characterized in that The total intrusion volume is at most 10 ml / g as measured by mercury porosimetry.

4. The polymer composition according to claim 1, characterized in that The total intrusion volume is between 1.2 ml / g and 10 ml / g.

5. The polymer composition according to claim 1 or 2, characterized in that The relative incremental intrusion for pore sizes above 10 μm is at most 85%.

6. The polymer composition according to claim 1 or 2, characterized in that The incremental intrusion between pore sizes of 10 μm and 1 μm is at least 0.15 ml / g.

7. The polymer composition according to claim 1 or 2, characterized in that The incremental intrusion between pore sizes of 10 μm and 0.1 μm is at least 0.15 ml / g.

8. The polymer composition according to claim 1 or 2, characterized in that The relative incremental intrusion between pore sizes of 10 μm and 1 μm is at least 10%.

9. The polymer composition according to claim 1 or 2, characterized in that The porous polymer powder POW1 has a volume median particle size D50 between 1 μm and 700 μm.

10. The polymer composition according to claim 1 or 2, characterized in that The apparent bulk density of the polymer powder POW1 is 0.1 g / cm 3 and 0.60g / cm 3 between.

11. The polymer composition according to claim 1 or 2, characterized in that The polymer powder POW1 comprises at least 60% by weight of polymer particles PAR1 of the polymer powder composition POW1.

12. The polymer composition according to claim 11, characterized in that The weight average particle size of the polymer particles PAR1 is between 15 nm and 900 nm.

13. The polymer composition according to claim 11, characterized in that The polymer particles PAR1 are multistage polymers MSP1 in the form of core-shell particles.

14. The polymer composition according to claim 11, characterized in that The polymer powder POW1 includes a multistage polymer MSP1 in the form of core-shell particles and a (meth)acrylic polymer MP1 in the form of polymer particles.

15. The polymer composition according to claim 11, characterized in that The polymer powder POW1 comprises at least 70% by weight of the polymer powder composition POW1 in terms of polymer particles PAR1.

16. The polymer composition according to claim 14, characterized in that The multistage polymer MSP1 has a multilayer structure, comprising: at least one stage (SA1) comprising a polymer (A1) having a glass transition temperature below 10°C, and at least one stage (SA2) comprising a polymer (A2) having a glass transition temperature above 60°C.

17. The polymer composition according to claim 1 or 2, characterized in that The polymer powder POW1 includes a multi-stage polymer MSP1 and a (meth)acrylic polymer MP1.

18. The polymer composition according to claim 4, characterized in that The total intrusion volume is between 1.25 ml / g and 8 ml / g.

19. The polymer composition according to claim 4, characterized in that The total intrusion volume is between 1.3 ml / g and 7 ml / g.

20. The polymer composition according to claim 4, characterized in that The total intrusion volume is between 1.35 ml / g and 6 ml / g.

21. The polymer composition according to claim 4, characterized in that The total intrusion volume is between 1.35 ml / g and 5 ml / g.

22. The polymer composition according to claim 4, characterized in that The total intrusion volume is between 1.35 ml / g and 4 ml / g.

23. The polymer composition according to claim 7, characterized in that The incremental intrusion between pore sizes of 10 μm and 0.1 μm is at least 0.2 ml / g.

24. The polymer composition according to claim 7, characterized in that The incremental intrusion between pore sizes of 10 μm and 0.1 μm is at least 0.25 ml / g.

25. A method for preparing a liquid polymer composition LCP1, comprising the following steps: a) providing a polymer composition according to any one of claims 1 to 24 in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g as measured according to mercury porosimetry, b) contacting the polymer composition in the form of porous polymer powder POW1 with a liquid composition LC1.

26. The method according to claim 25, characterized in that The viscosity of the liquid composition LC1 at a temperature of 25° C. is between 0.5 mPa*s and 1000 Pa*s.

27. The method according to claim 25 or 26, characterized in that The liquid composition LC1 is selected from compositions for preparing vinyl ester, unsaturated polyester or epoxy resin; or it is a styrene monomer or a (meth)acrylic monomer, or a mixture thereof, or a liquid composition comprising the monomer.

28. The method according to claim 25 or 26, characterized in that The weight percentage of the porous polymer powder POW1 in the liquid polymer composition LCP1 is between 0.5 wt % and 50 wt %.

29. Use of a polymer composition according to any one of claims 1 to 24 or a composition obtained by a process according to any one of claims 25 to 28 as an impact modifier or an impact modified composition.

30. Method for reducing the dispersion time of a polymer powder in a liquid by providing a polymer composition according to any one of claims 1 to 24 in the form of a porous polymer powder POW1 having a total intrusion volume of at least 1.2 ml / g measured according to mercury porosimetry.

31. The method according to claim 30, comprising the steps of: - providing a precursor of a thermosetting polymer or a monomer of a thermoplastic polymer, - bringing into contact said polymer composition in the form of porous polymer powder POW1 with said precursor.

32. The method according to claim 31, characterized in that The precursor is a liquid.

33. The method according to claim 31, characterized in that The precursor is a liquid with a viscosity between 0.5 mPa*s and 1000 Pa*s at a temperature of 25°C.

34. The method according to claim 31, characterized in that Between 0.5 and 100 parts by weight of the porous polymer powder POW1 are contacted with 100 parts by weight of the precursor.

35. Use of a polymer composition according to any one of claims 1 to 24 as a composition for reducing dispersion time.

Citation Information

Patent Citations

  • Vinylidene fluoride polymer powder and use thereof

    EP2196479A1

  • Acrylic polymer powder, acrylic sol and molding

    US20040147668A1

  • Liquid composition comprising a multistage polymer, its method of preparation and its use

    WO2017121749A1

  • Vinylidene fluoride polymer powder and use thereof

    CN101821298A

  • Acrylic acid polymer powder, acrylic acid sol and forming article

    CN1517400A